Technology in Mathematics Teaching and Learning: An Impact Evaluation in Selected Senior Schools in Masingbi Town - Karim, Samuel; Zoker, Exton Mohamed (Assyfa Learning Journal, 2023)
The analysis is based on a detailed evaluation of primary data collected through case studies, questionnaires, and semi-structured interviews in Senior secondary schools in Masingbi. Mathematics education learning is explored to understand the issues surrounding Technology integration. This study shows that despite the perceived advantages of Technology integrated teaching and learning methods, there are barriers closely connected to teachers’ teaching beliefs at work. Most educators admitted the lack of ongoing professional training programs and curriculum expectations as among the factors that affect their attitudes towards Technology in their respective Teaching and learning schools. Further empirical research is suggested to advance the exploration of the role of subject leaders in Technology -integrated Teaching and learning methods. This research provides an in-depth analysis of the exploration of own practice and mathematics teachers' perceptions on integrating Technology into teaching. The total sample size of respondents was sixty (60), and both simple random sampling technique was used to develop samples of Teachers and Pupils, while a purposive sampling technique was used to develop the sample for the Principals or Heads of Schools of the three selected senior schools in Masingbi as respondents